Early initiation of breastfeeding, colostrum avoidance, and their associated factors among mothers with under one year old children in rural pastoralist communities of Afar, Northeast Ethiopia: a cross sectional study - Gebretsadkan Gebremedhin Gebretsadik; Helen Tkuwab; Kidanemaryam Berhe; Afework Mulugeta; Hajira Mohammed; Abebe Gebremariam (BMC, 2020)
Abstract Background Early initiation of breastfeeding (EIBF) is defined as initiation of breastfeeding within 1 h of birth. This is also the time colostrum is secreted with its potential benefits. Globally, two out of five under 5 children die in the first month of life, more than a third of which being on the first day. Neonatal mortality is still a major health problem in Ethiopia. EIBF and colostrum feeding are associated with decreased neonatal morbidity and mortality. With this study, we aim to determine the magnitude and factors associated with EIBF and colostrum avoidance. Methods A community based cross-sectional study was conducted from May to June 2016 on 390 mothers in Afar region. Bivariate logistic regression was used to identify the association between the independent and the outcome variables. Multivariable logistic regression was used to determine the independent predictors of EIBF and colostrum avoidance. The strength of the association was measured by odds ratio and 95% confidence interval, and p-value < 0.05 was considered statistically significant. Hosmer and Lemeshow test was used to test model goodness of fitness and multi-collinearity between independent variables was checked. Results About 248(63.6%) respondents initiated breastfeeding within 1 h of birth. Mothers whose delivery was attended by a health professional had 4.75 times higher odds (AOR 4.75; 95% CI 1.71, 13.19) of EIBF as compared to those who were attended by others. Trust on nurses to provide pregnancy care (AOR 5.59; 95% CI 1.05, 29.8) was significantly associated with EIBF. About 300(76.9%) respondents discarded colostrum. Mothers who had no discussion with TBA on child nutrition were 6.6 times (AOR 6.63; 95% CI 1.43, 30.63) more likely to avoid colostrum than their counterparts. Conclusion More than one-third of infants didn't start breastfeeding within 1 h of birth and three-fourth of the mothers discarded colostrum. Therefore, it is important to develop and/or strengthen services/advice on EIBF including colostrum feeding. Promoting delivery by health professionals, discussion on child nutrition and building trust between mothers and health professionals can be important community interventions to encourage EIBF and colostrum feeding.